Polyzosteria cockroaches in Tasmania (Blattodea: Blattidae: Polyzosteriinae) represent a new, endemic species, with allopatric alpine and coastal sub-populations - Henry, Shasta C.; Cameron, Stephen L.; Smolenski, Adam; Mcquillan, Peter (Zootaxa, 2021)
We describe the endemic Tasmanian cockroach, Polyzosteria yingina sp. nov. (Henry), 78 years after it was first documented. Evidence from morphology, biogeography and CO1 barcodes is used to distinguish this species from related mainland Australian taxa it has previously been confused with. Polyzosteria yingina sp. nov. has two strongly allopatric populations: a compact alpine population above 1000m and a dispersed east coastal one at sealevel. However, mitochondrial Control Region D-loop molecular analysis suggests a single species identity for these disparate populations. Detailed internal and external morphological descriptions and photographs of living and preserved type material are presented. We also speculate on some hypotheses which could account for the unusual distribution of this charismatic insect.